2022
DOI: 10.3390/ma15207062
|View full text |Cite
|
Sign up to set email alerts
|

Alloying Elements Effect on the Recrystallization Process in Magnesium-Rich Aluminum Alloy

Abstract: This paper addresses the study of the complex effect of alloying elements (magnesium, manganese, copper and zirconium) on changes in magnesium-rich aluminum alloy composition, fine and coarse particle size and number, recrystallization characteristics and mechanical properties. The data obtained made it possible to analyze change in the chemical composition, sizes of intermetallic compounds and dispersoids depending on alloying elements content. The effect of the chemical composition on the driving force and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Research findings have indicated that the incorporation of aluminum (Al) elements within the concentration range of 1% to 5% significantly enhances the microstructure of the material. As a result, the application of this technique is commonly observed in the context of magnesium alloy, with the aim of improving its mechanical properties and resistance to corrosion [65], [66]. The corrosion resistance of magnesium alloy can be enhanced by augmenting its aluminum content.…”
Section: Medical Application Of Biodegradable Magnesium Alloymentioning
confidence: 99%
“…Research findings have indicated that the incorporation of aluminum (Al) elements within the concentration range of 1% to 5% significantly enhances the microstructure of the material. As a result, the application of this technique is commonly observed in the context of magnesium alloy, with the aim of improving its mechanical properties and resistance to corrosion [65], [66]. The corrosion resistance of magnesium alloy can be enhanced by augmenting its aluminum content.…”
Section: Medical Application Of Biodegradable Magnesium Alloymentioning
confidence: 99%
“…A higher SFE is beneficial for dynamic recovery and dynamic recrystallization. Thus, dynamic recovery of the β-Li phase readily occurs during the rolling process, and the release of dislocation entanglement energy promotes the DRX of the β-Li phase [31,32]. Dynamic recrystallization of the β-Li phase occurs during each 30% reduction rolling cycle.…”
Section: Influence Of Rolling Passes On the Microstructure Evolution ...mentioning
confidence: 99%